Trichoderma spp. capable of growing at low temperatures with biocontrol potential - Szakacs G; Tavaszi A (浙江大学学报. 农业与生命科学版, 2004)
Though there are successful commercial biocontrol products with Trichoderma spp. in many countries including US, Israel and Europe, their usefulness is limited in cold environments such as mid-and northern part of Europe, US and Canada, especially in the late fall, winter and early spring period. Trichoderma isolates capable of growing at low temperatures (5-10 ℃) and showing good antagonistic properties against plant pathogenic fungi may have therefore both scientific and commercial value.Altogether 25 Trichoderma strains have been isolated from 18 soil samples at 10 ℃ on two different agar media (potato-dextrose-agar and cellulose-agar supplemented with doxycycline). The incubation period was 6 weeks at 10 ℃ in the first isolation step then shorter (3 weeks) when the pure cultures were obtained. Soils resulting in positive isolates are originating from Russia (lake Baikal area, lake Ladoga area), Finland (Espoo), US (South Dakota, Rocky Mountains in Colorado) and Canada (Vancouver area). Dual culture (confrontation assay) experiments have been performed with the 23“cold-tolerant” Trichoderma strains at 18 ℃ against four plant pathogenic fungi (Botrytis cinerea, Fusarium oxysporum f. sp. dianthi, Rhizoctonia solani and Sclerotinia sclerotiorum). Three strains showing good mycoparasitism were propagated in solid substrate fermentation at 18 ℃ on wheat bran-crude chitin mixture medium. The temperature optimum of chitinase enzyme produced by strain TUB F-1173 (isolation source: prairie soil, South Dakota) is around 20 ℃.